A Behavioral Health Program for Alcohol Use Disorder, Substance Abuse, and Depression in Chronic Liver Disease. Issue 5 (12th March 2019) - Verma, Manisha; Horrow, Jay; Navarro, Victor
Abstract : Alcohol use disorder, substance abuse, and depression are illnesses that deteriorate the quality of life (QOL) of patients with chronic liver disease (CLD). Screening and behavioral health programs integrated into routine practice can mitigate the deleterious effects of such illnesses but have not been adopted in hepatology practices. We implemented a behavioral health program based on the Screening, Brief Intervention, and Referral to Treatment (SBIRT) model and assessed its acceptability and effectiveness in improving QOL. This was a quality improvement study. Patients with CLD and a scheduled outpatient visit in the hepatology clinic were screened while waiting for their appointment. All patients who screened positive for any of the three illnesses were offered a brief intervention (BI) at the point of care and at 3 months by a trained social worker. The BI used the principles of motivational interviewing and cognitive behavioral therapy. Severity of illness was assessed at baseline, 3 months, and 6 months. Participants completed an acceptability survey at 6 months. We screened 303 patients; 61.7% were positive for any of the three illnesses assessed. Among the positive patients, depression was most common (48.4%), alcohol and substance abuse were each 26%. For the 95 patients who underwent BI, QOL improved from baseline to 3 and 6 months ( P < 0.001) and patients with depression improved the most. Depression was the only independent predictor of change in QOL over time. Of the enrolled patients, 82% agreed BIs improved their overall care and 87% indicated a desire to continue with the behavioral program. Conclusion: An outpatient behavioral health program based on the SBIRT model is acceptable to patients with CLD and may help improve QOL over time. Abstract : Alcohol use disorder, substance abuse, and depression are illnesses which deteriorate the quality of life (QOL) of chronic liver disease (CLD) patients. Integrating screening and brief interventions in Hepatology ambulatory settings can mitigate the deleterious effects of such illnesses. This study shows the acceptability of an integrated behavioral health program, based on the evidence based SBIRT (Screening, Brief Intervention and Referral to Treatment) approach.